PENGEMBANGAN KEWIRAUSAHAAN BERBASIS PRODUK KREATIF DI SMP AL JANNAH, PONDOK RANGON, JAKARTA TIMUR - Mei Ie; Atalya Fransiska (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2022)
Awareness to develop creativity and innovation from a young age has increased. Every child is born with creative potential. Therefore, children need to be guided and directed to develop their creative potential optimally. In an effort to develop creativity through entrepreneurship programs, positive activities that contain creative ideas are needed. One of the positive activities held by community service partners, in this case is SMP Al-Jannah Islamic, Nature, and Science School located in Pondok Rangon, East Jakarta is to hold seminars and entrepreneurship workshops regularly every semester. The procurement of seminars and workshops also shows that the school aims to create a diverse learning environment, which can increase the self-efficacy of students and provide opportunities for students to develop their potential and abilities. The external target that will be generated from this PKM is in the form of knowledge transfer about entrepreneurship and creative product creation, which can be applied in Al-Jannah Islamic Junior High School, Nature, and Science School. In addition, this PKM activity is also expected to be able to develop the interest of Al-Jannah Islamic, Nature, and Science School junior high school students towards the entrepreneurial profession as one of the professional choices in the future. The method of implementation of activities is to conduct in-depth-interview,studyrelevant literature, draw up a plan of mentoring activities, implementation of PKM activities, evaluation of activities, as well as the preparation and submission of activity reports. The result of this activity is an increase in students' insights regarding entrepreneurship. From workshop activities, students also gain technical skills regarding the manufacture of creative products in the form of therapeutic scent candles. ABSTRAK:Kesadaran untuk mengembangkan kreativitas dan inovasi sejak usia muda sudah makin meningkat. Pada dasarnya setiap anak dilahirkan dengan membawa potensi kreatif. Oleh karena itu, anak perlu dibimbing dan diarahkan untuk mengembangkan potensi kreatifnya tersebut secara optimal. Dalam upaya mengembangkan kreativitas melalui program kewirausahaan, maka diperlukan aktivitas-aktivitas positif yang mengandung ide kreatif. Salah satu kegiatan positif yang diadakan oleh pihak mitra kegiatan pengabdian kepada masyarakat, dalam hal ini adalah SMP Al-Jannah Islamic, Nature, dan Science School yang berlokasi di Pondok Rangon, Jakarta Timur adalah mengadakan kegiatan seminar dan workshop kewirausahaan secara rutin setiap semesternya. Pengadaan kegiatan seminar dan workshop ini juga menunjukkan bahwa pihak sekolah bertujuan menciptakan lingkungan pembelajaran yang beragam, yang dapat meningkatkan efikasi diri para siswa dan memberikan kesempatan kepada para siwa untuk mengembangkan potensi dan kemampuan diri. Target luaran yang akan dihasilkan dari PKM ini adalah berupa transfer pengetahuan mengenai kewirausahaann dan pembuatan produk kreatif, yang dapat diterapkan di SMP Al-Jannah Islamic, Nature, dan Science School. Selain itu, kegiatan PKM ini juga diharapkan mampu mengembangkan minat siswa SMP Al-Jannah Islamic, Nature, dan Science School terhadap profesi wirausaha sebagai salah satu pilihan profesi di masa mendatang. Metode pelaksanaan kegiatan adalah melakukan in-depth-interview, studi literatur yang relevan, menyusun rencana kegiatan pendampingan, pelaksanaan kegiatan PKM, evaluasi kegiatan, serta penyusunan dan penyerahan laporan kegiatan. Hasil kegiatan ini adanya peningkatan wawasan siswa mengenai kewirausahaan. Dari kegiatan workshop, para siswa juga mendapatkan keterampilan teknis mengenai pembuatan produk kreatif berupa lilin aroma terapi.